Quality Indicators for the Diagnosis and Management of Acute Bacterial Rhinosinusitis. Issue 4 (July 2020) - Cottrell, Justin; Yip, Jonathan; Chan, Yvonne; Chin, Christopher J; Damji, Ali; de Almeida, John R.; Desrosiers, Martin; Eskander, Antoine; Janjua, Arif; Kilty, Shaun; Lee, John M.; Macdonald, Kristian I.; et al.
Background: Acute bacterial rhinosinusitis (ABRS) is a highly prevalent disease that is treated by a variety of specialties, including but not limited to, family physicians, emergency physicians, otolaryngology—head and neck surgeons, infectious disease specialists, and allergy and immunologists. Unfortunately, despite high-quality guidelines, variable and substandard care continues to be demonstrated in the treatment of ABRS. Objective: This study aimed to develop ABRS-specific quality indicators (QIs) to evaluate the diagnosis and management that reduces symptoms, improves quality of life, and prevents complications. Methods: A guideline-based approach, proposed by Kötter et al., was used to develop QIs for ABRS. Candidate indicators (CIs) were extracted from 4 guiding documents and evaluated using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool. Each CI and its supporting evidence was summarized and reviewed by an expert panel based on validity, reliability, and feasibility of measurement. Final QIs were selected from CIs utilizing the modified RAND/University of California at Los Angeles appropriateness methodology. Results: Twenty-nine CIs were identified after literature review and evaluated by our panel. Of these, 5 CIs reached consensus as being appropriate QIs, with 1 requiring additional discussion. After a second round of evaluations, the panel selected 7 QIs as appropriate measures of high-quality care. Conclusion: This study proposes 7 QIs for the diagnosis and management of patients with ABRS. These QIs can serve multiple purposes, including documenting the quality of care; comparing institutions and providers; prioritizing quality improvement initiatives; supporting accountability, regulation, and accreditation; and determining pay for performance initiatives.